Applying a Common-Sense Approach to Fighting Obesity. (28th June 2012) - Breland, Jessica Y.; Fox, Ashley M.; Horowitz, Carol R.; Leventhal, Howard
Abstract : The obesity epidemic is a threat to the health of millions and to the economic viability of healthcare systems, governments, businesses, and nations. A range of answers come to mind if and when we ask, "What can we, health professionals (physicians, nurses, nutritionists, behavioral psychologists), do about this epidemic?" In this paper, we describe the Common-Sense Model of Self-Regulation as a framework for organizing existent tools and creating new tools to improve control of the obesity epidemic. Further, we explain how the Common-Sense Model can augment existing behavior-change models, with particular attention to the strength of the Common-Sense Model in addressing assessment and weight maintenance beyond initial weight loss.